Significance of Metabolic Tumor Volume and Total Lesion Glycolysis Measured Using (18)F-FDG PET/CT in Locally Advanced and Metastatic Gallbladder Carcinoma - Chun, You Jin (Yonsei Med J, 2019)
PURPOSE: This study aimed to determine the prognostic value of new quantitative parameters of (18)F-fluorodeoxyglucose positron emission tomography/computed tomography ((18)F-FDG PET/CT), including metabolic tumor volume (MTV), in patients with locally advanced and metastatic gallbladder cancer (GBC). MATERIALS AND METHODS: In total, 83 patients initially diagnosed with locally advanced and metastatic GBC and who underwent (18)F-FDG PET/CT at the time of initial diagnosis were retrospectively reviewed. The metabolic volume-based PET parameters of primary tumors and metastatic lesions were measured, including maximum and average standardized uptake values (SUV), MTV, and total lesion glycolysis. An overall survival (OS) analysis was performed using the Kaplan-Meier method with PET and clinical parameters. A Cox proportional hazards regression analysis was performed to determine independent prognostic factors. RESULTS: In univariate analysis, pathologic differentiation (p<0.001), performance status (PS; p=0.003), C-reactive protein (CRP) level (p=0.009), and PET-related SUV(mt max) (the highest SUV among the metastatic lesions) (p=0.040) and MTV(total) (the sum of the MTVs of both the primary and metastatic lesions) (p=0.031), were significant for OS. In multivariate analysis, MTV(total) (hazard ratio: 2.07; 95% confidence interval: 1.23–3.48; p=0.006) remained significant for the prediction of OS, as did differentiation (p=0.001), PS (p=0.001), and CRP (p=0.039). CONCLUSION: In locally advanced and metastatic GBC, volume-based PET/CT parameters of the total tumor burden of malignancy, such as MTV(total), were found to be useful for the identification of patients with poor prognosis.